A novel approach to assess the spontaneous gastrointestinal bleeding risk of antithrombotic agents using Apcmin/+ mice - Wei, Huijun; Shang, Jin; Keohane, CarolAnn; Wang, Min; Li, Qiu; Ni, Weihua; O’Neill, Kim; Chintala, Madhu (Thrombosis and Haemostasis, 2014)
Assessment of the bleeding risk of antithrombotic agents is usually performed in healthy animals with some form of vascular injury to peripheral organs to induce bleeding. However, bleeding observed in patients with currently marketed antithrombotic drugs is typically spontaneous in nature such as intracranial haemorrhage (ICH) and gastrointestinal (GI) bleeding, which happens most frequently on top of preexisting pathologies such as GI ulcerations and polyps. Apcmin/+ mice are reported to develop multiple adenomas through the entire intestinal tract and display progressive anaemia. In this study, we evaluated the potential utility of Apcmin/+ mice as a model for assessing spontaneous GI bleeding with antithrombotic agents. Apcmin/+ mice exhibited progressive blood loss starting at the age of nine weeks. Despite the increase in bleeding, Apcmin/+ mice were in a hypercoagulable state and displayed an age-dependent increase in thrombin generation and circulating fibrinogen as well as a significant decrease in clotting times. We evaluated the effect of warfarin, dabigatran etexilate, apixaban and clopidogrel in this model by administering them in diet or in the drinking water to mice for 1–4 weeks. All of these marketed drugs significantly increased GI bleeding in Apcmin/+ mice, but not in wild-type mice. Although different exposure profiles of these antithrombotic agents make it challenging to compare the bleeding risk of compounds, our results indicate that the Apcmin/+ mouse may be a sensitive preclinical model for assessing the spontaneous GI bleeding risk of novel antithrombotic agents.
Keywords: Antithrombotic; spontaneous; gastrointestinal; bleeding; Apcmin/+ mice